Libya in the wider world - Joffé, E. G. H.; Tondini, Matteo; Pellitteri, Antonino; Isidoros, Konstantina; Pack, Jason (The journal of North African studies, 2011)
[ ...] Paoletti, Emanuela: Migration and foreign policy : the case of Libya. - S. 215-231 Joffé, George: Libya and the European Union : shared interests? - S. 233-249 [ ... } Pellitteri, Antonino: Al-dawla al-fātimiyya : politics, history and the re-interpretation of Islam. - S. 263-273 Zoubir, Yahia H.: The United States and Libya : the limits of coercive diplomacy. - S. 275-297 [ ... ]